An improved energy storage switched boost grid‐connected inverter for photovoltaic applications. Issue 2 (24th September 2022) - Liu, Shuo; Zhou, Xu; Li, Jianlin; Li, Chengxin; Liu, Chenguang
Abstract: When the traditional two‐stage boost inverter is used in photovoltaic (PV) and energy storage systems, it is necessary to connect additional bidirectional conversion devices, which will increase the loss of the system and increase the complexity of system control. Therefore, an improved energy storage switched boost (ESSB) grid‐connected inverter is proposed in this paper. The system has the advantages of high integration, high gain and dead time immunity. By controlling the duty cycle of the system, the energy management of the battery can be realized. The system consists of three parts: PV cells, ESSB network and grid‐connected inverter. In order to maximize the energy utilization, this paper uses the disturbance observation method to track the maximum power point of PV cells, and formulates a set of energy management strategy to control the energy flow between the three energy units. Simulation and experiments verify the superiority of the topology and the feasibility of the energy storage strategy.